2020
DOI: 10.1155/2020/7847526
|View full text |Cite
|
Sign up to set email alerts
|

Heightened ACE Activity and Unfavorable Consequences in COVID-19 Diabetic Subjects

Abstract: Coronavirus disease-19 (COVID-19) can manifest as fever, cough, and shortness of breath and is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Occasionally, these patients may present with diabetic ketoacidosis (DKA). Patients with comorbidities such as diabetes mellitus and hypertension, as well as older age groups, are known to have a more severe disease progression and poor prognosis. In this review article, we attempt to better understand the disease process in diabetics and also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
2
12
0
1
Order By: Relevance
“…Our analysis demonstrated that asymptomatic children with diabetes and/or recent contact with a COVID-19 case, as well as those tested for surveillance purposes (rather than for pre-procedure or pre-admission purposes), had significantly higher estimated risk of being in the quartile with the highest viral burden. Despite small numbers of diabetic patients in our study, the finding that diabetic children were more at risk of having high viral loads requires further dedicated investigation, as it is consistent with studies in adults that have demonstrated more severe disease and poorer prognosis in patients with diabetes (14,15). The asymptomatic population with known/recent COVID-19 contact overlapped with the population tested for surveillance purposes, though not perfectly (as some pre-procedure or pre-admission patients had contacts).…”
Section: Resultssupporting
confidence: 87%
“…Our analysis demonstrated that asymptomatic children with diabetes and/or recent contact with a COVID-19 case, as well as those tested for surveillance purposes (rather than for pre-procedure or pre-admission purposes), had significantly higher estimated risk of being in the quartile with the highest viral burden. Despite small numbers of diabetic patients in our study, the finding that diabetic children were more at risk of having high viral loads requires further dedicated investigation, as it is consistent with studies in adults that have demonstrated more severe disease and poorer prognosis in patients with diabetes (14,15). The asymptomatic population with known/recent COVID-19 contact overlapped with the population tested for surveillance purposes, though not perfectly (as some pre-procedure or pre-admission patients had contacts).…”
Section: Resultssupporting
confidence: 87%
“…The association between COVID-19 and hyperglycemia in elderly patients with T2D might reflect metabolic inflammation and exaggerated cytokine release. SARS-CoV2 infection can deteriorate glycemic control by enhancing insulin resistance and impaired insulin secretion, thus leading to DKA [11,55]. The unique interactions between SARS-CoV-2 and the RAAS might provide yet another mechanism in the pathophysiology of DKA first by direct entry of SARS-CoV-2 into pancreatic islet cells worsening b-cell injury, and second by downregulation of ACE2 after viral entry that can lead to unopposed angiotensin II and subsequent insulin secretion impedance [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…The association between Covid-19 and hyperglycemia in elderly patients with T2D might reflect metabolic inflammation and exaggerated cytokine release. SARS-CoV2 infection can deteriorate glycemic control, involving both profound insulin resistance and impaired insulin secretion, together leading to DKA and increasing hospital admissions and mortality [10,92].…”
Section: Discussionmentioning
confidence: 99%